PEMBANGUNAN E-COMMERCE (PENJUALAN ONLINE) PADA TURPEZ SHOP - Agung Wahana; Irvan Purliansyah (Jurnal Computech & Bisnis (e-Journal), 2015)
The purpose of this research is to develop the Electronic Commerce ( E - Commerce ) for the sale of clothing online using internet technology and facilities payment through Paypal . System development method used is Waterfall with Flowmap analysis tools , Data Flow Diagrams ( DFD ) and Entity Relationship Diagram ( ER - D ) . The results of this study is an information system that handles transaction ordering , payment can be made by transfer of money between banks and through Paypal , Shipments and returns facilities that can help customers to obtain information about products offered by Turpez Shop , enabling customers in the process ordering products , and can help increase sales for the company . Keywords: E - Commerce , Paypal , Waterfall